Innovative services for informing visually impaired persons in indoor environments - Peraković, Dragan; Periša, Marko; Cvitić, Ivan; Brletić, Luka (EAI Endorsed Transactions on Internet of Things, 2018)
Movement and informing visually impaired persons is difficult because mobile application solutions and services are unable to work in indoors environments (location based service using GPS technology). Main precondition for active participation in the daily living and needs of visually impaired persons is increased degree of mobility. The aim of this research is to increase the quality of life of visually impaired persons and the degree of mobility in indoor environments by applying modern information and communication technologies (Cloud Computing, Fog, IoT, AAL / ELE platform). User requirement will be used to define functionalities of service for informing visually impaired persons in the example of large retail chains. A conceptual system architecture model will be proposed for providing information service with the aim to provide real-time information to users. This research will also show simulation testing of the proposed architecture with Arduino Uno and Raspberry Pi 3 platforms for collecting information and informing end users.